Pemodelan Persebaran Emisi Udara di Kawasan Industri Pelabuhan Tanjung Perak - Komang Kurniawan (Prosiding ESEC, 2023)
The maritime industry in Indonesia is increasing every year, especially in the maritime service sector. Tanjung Perak Port is one of the areas in Surabaya whose operational activities focus on the maritime service sector. The operational activities of the maritime service sector produce emissions from both ship chimneys and chimneys resulting from the burning of raw materials for the maritime service industry. To find out directly the emissions produced, a test was carried out on the chimney at one of the maritime service sector companies. Measurements were made by testing the parameter concentration of SO2. From the measurement results obtained, it will be modeled into the aeromod software so that the distribution of emissions generated around the maritime service industry area can be known. After modeling it in the AERMOD software, the results show that the concentration of SO2 produced by the maritime service industry has been dispersid from a distance of 500 meters from the chimney resulting from the combustion of raw materials for the maritime service industry. With the results obtained, the solution to reduce the concentration of SO2 produced is to modify the chimney that produces emissions so that the emissions produced can be reduced and the emission distribution area can be reduced so that it does not have a wide impact on the surrounding area